2020
DOI: 10.7821/naer.2020.7.575
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric and Collaborative Network Analysis on Active Methodologies in Education

Abstract: Teachers have gradually been making more use of active methodologies at all educational levels, and some even carry out research in this area. The objective of this research was to develop a bibliometric study in order to gain an in-depth view of the scientific literature on active methodologies in education. An analysis of the classic descriptions of bibliometrics, co-authorship indexes and collaboration networks was carried out, using documents indexed by the Web of Science on active methodologies in educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 39 publications
1
16
0
2
Order By: Relevance
“…From 2016 onwards, the production increased in a significant manner, being the production of more than 200 documents each year. As other studies highlighted, it has been found that English is the most publishing language, becoming this one the scientific language worldwide [51,[59][60][61]. Apart from this, WOS has its own penalties when published documents are not in [14].…”
Section: Discussionmentioning
confidence: 99%
“…From 2016 onwards, the production increased in a significant manner, being the production of more than 200 documents each year. As other studies highlighted, it has been found that English is the most publishing language, becoming this one the scientific language worldwide [51,[59][60][61]. Apart from this, WOS has its own penalties when published documents are not in [14].…”
Section: Discussionmentioning
confidence: 99%
“…It is, therefore, vitally important to develop active learning methodologies and a flexible approach to time management. As its name suggests, active methodologies are based on making students participate during their learning process [13]. Felder and Brent offered a more restrictive definition, but perhaps a more useful one: "Active learning consists of short course-related individual or small-group activities that all students in a class are called upon to do, alternating with instructor-led intervals in which student responses are processed and new information is presented" [14].…”
Section: Flipped Classroom As An Active Learning Methodologymentioning
confidence: 99%
“…Pedagogical strategies must respond to the new needs and demands of the students, making feasible the hybridization of the classic models (magisterial sessions, conferences) and the incorporation of innovations linked to active methodologies (flipped classroom, gamification, etc.). These strategies foster curiosity, creativity, and motivation [1,2], making students active protagonists of their learning. Among all the possibilities within the active methodologies, we will focus our interest on the flipped classroom.…”
Section: Introductionmentioning
confidence: 99%